Remapping EMU: On the future construction of economic and monetary union - Stefan Ederer; Stefan Weingärtner (WWWforEurope, 2013)
The economic crisis has laid open deficiencies in the construction of the European Economic and Monetary Union. At its foundation, it was assumed that monetary integration would reduce the likelihood of asymmetric shocks. The crisis shows, however, that endogenous mechanisms may even amplify existing asymmetries. Without a lender of last resort, a common regulation and supervision of banks, a common fiscal policy and a co-ordinated economic policy the European Monetary Union is incomplete. The European Council and the Commission have proposed reforms for the completion of Economic and Monetary Union. Among these proposals are the implementation of a Banking Union and an integrated economic and fiscal policy. In the long run, national government debt is to be mutualised at the European level. A European fiscal capacity shall be combined with an automatic transfer mechanism between member countries, in order to smooth business cycle differentials. Further proposals are intended to accelerate in future structural reforms by the member countries along the lines of the country-specific recommendations issued by the Commission and the Council. A first step towards creating an integrated Banking Union has been taken by the introduction, albeit in an attenuated version, of a common bank supervision. However, key elements to secure the stability of the euro area are still missing. Measures recently decided under the acute pressure of the crisis ("Six-pack", "Twopack", "Fiscal compact", "Euro-plus Pact") are confined to structural reform and have de-facto suspended the operation of automatic stabilisers in the crisis countries. This severely undermines popular support in debtor and creditor countries alike for Economic and Monetary Union, to the point of jeopardising its existence.
Keywords: E61; E62; F15; 330; European Integration; European Economic Policy; Strukturwandel; Politische Reform; Wirtschaftsreform; Eurozone; EU-Staaten